ENVIRONMENTAL PROCEDURAL LAW: COLLECTIVE CIVIL JURISDICTION. PROCEDURAL ASPECTS.: JURISDIÇÃO CIVIL COLETIVA. ASPECTOS PROCESSUAIS. (REMUNOM, 2025)
The environment is the set of natural and artificial elements that make up the space in which all living beings reside, encompassing components such as soil, water, air, fauna, flora, and ecosystems. Thus, it is essential for the survival and well-being of all living beings, serving as a source of essential resources like water, food, and oxygen, as well as playing a vital role in climate regulation and ecological cycles. In this context, Environmental Law emerges as a branch of law aimed at protecting and conserving the environment, seeking to ensure the sustainability of natural resources and ecological balance for the benefit of present and future generations. Consequently, Environmental Procedural Law emerges as a fundamental branch for the enforcement of diffuse rights related to the environment, focusing on ensuring that collective interests are judicially protected. Therefore, this scientific article aims to discuss Environmental Procedural Law, considering issues pertinent to collective civil jurisdiction and certain procedural aspects, particularly those related to the main judicial means of environmental protection, such as: public civil action, popular action, collective writ of mandamus, and writ of injunction.